Seasonal Availability of Non-timber Forest Products Collected by the Tribals in Gandigadha Reserve Forests of District Mayurbhanj, Orissa - Rout, S. D.; Panda, S. K. (Indian Forester, 2011)
Non-timber Forest Products (NTFP) contribute an integral component of the food for the communities dependent on forests. Their role becomes more significant for less agricultural dependent communities with small land holding residing in remote forests. Fifty-four important NTFP species have been reported to be collected by the villagers in Gandigadha for consumption. However, a few new species like 'Sal' (Shorea robusta) leaves, tooth stick and seeds 'Mahula' (Madhuca indica) flower and fruit, 'Chara' (Buchanania lanjan) fruits, seeds and mushroom are collected and sold to local traders.